A comparative study of spatial variation between the states of Peninsular Malaysia in terms of water supply characteristics and consumer’s perception - Phang, Wai Leng; Chan , Ngai Weng (2015)

(untitled)
Peninsular Malaysia is made up of 11 states with different landforms, natural resources, population patterns and lifestyle patterns. This paper aims to compare the spatial variations between water supply characteristics in terms of price, non-revenue water (NRW) and domestic water consumption by states and domestic water consumers’ perception in terms of their satisfaction of their water service suppliers. The methodology is based on both primary and secondary data. Primary data is derived from a questionnaire survey on 400 domestic water consumers and secondary data obtained through a survey of books, articles, journals, annual reports and official websites that are related to water issues. The results conclude that different states show different levels of performance by various water service suppliers and different perception amongst consumers which is caused by spatial variation.